Geographical analysis of equatorial plasma bubbles by GPS and nightglow measurements. Issue 9 (1st November 2015) - Nade, D.P.; Shetti, D.J.; Sharma, A.K.; Taori, A.; Chavan, G.A.; Patil, P.T.; Ghodpage, R.N.; Gurav, O.B.; Nikte, S.S.
Abstract This work about the zonal drift velocity and signature of equatorial plasma bubbles (EPBs) by measurements of global positioning system (GPS) receiver and all sky imager (ASI) operating in India, at the low latitude region. The optical and radio observations have been made from Kolhapur (16.8° N, 74.2° E) and Hyderabad (17.37°N, 78.48°E), respectively. The zonal drift velocity of EPBs has estimated using images of nightglow OI 630.0 nm emission recorded by ASI at Kolhapur. The measurements of total electron content (TEC) using the GPS have carried from the nearby station, Hyderabad. When depletions occurred about 00:37 h (IST) in TEC, the EPBs were found to occur about 5:30 h in optical data of OI 630.0 nm emission. This work focuses on simultaneous measurements of TEC and intensity of OI 630.0 nm emissions for EPBs during nighttime. The occurrence period of EPBs in TEC and OI 630.0 nm has found to be different. To study this difference, the zonal drift velocity of EPBs has established. The averaged eastward velocity of EPBs was found to be 138 m/s. The calculated values of zonal drift velocities are well correlated with that of the empirical model values. This work may be helpful in finding the growth of EPBs over low latitude.